Turmeric Herbal Remedies Significantly Reduce Dysmenorrhea in Indonesian Adolescents: Obat Herbal Kunyit Secara Signifikan Kurangi Dismenore pada Remaja Indonesia - Gita, Prigi Dewi; Kusumawardani, Paramitha Amelia; Hanum, Sri Mukhodim Farida; Rosyidah, Rafhani (Universitas Muhammadiyah Sidoarjo, 2024)
General background: Dysmenorrhea, or menstrual pain, is a condition that disrupts adolescents' daily activities, with prevalence ranging from 16.8% to 81%. It is commonly managed through pharmacological and non-pharmacological approaches. Specific background: High school students frequently experience dysmenorrhea, which can interfere with their school performance and well-being. Various non-pharmacological methods, such as herbal remedies and thermal therapies, have been proposed to alleviate symptoms. Knowledge gap: Despite the prevalence of dysmenorrhea, limited research focuses on the effectiveness of non-pharmacological interventions among high school students in Indonesia. Aims: This study aims to describe the severity of dysmenorrhea and the methods of pharmacological and non-pharmacological management among female students of SMA Dharma Wanita 1 Gedangan. Results: This quantitative descriptive study, involving 46 tenth-grade students, revealed that 67.4% of respondents experienced mild dysmenorrhea. Among non-pharmacological treatments, 69.6% consumed turmeric herbal remedies, 15.2% used warm compresses, and 10.9% applied warming lotions. Novelty: The study highlights that all non-pharmacological methods effectively reduced the severity of dysmenorrhea among the students, with turmeric herbal remedies being the most popular choice. Implications: These findings suggest the need for collaboration between healthcare professionals, educational authorities, and schools to provide health education on dysmenorrhea management for female adolescents. Highlights: Prevalence: 67.4% of students had mild dysmenorrhea. Treatment: 69.6% used turmeric herbal remedies for pain relief. Recommendation: Promote school-healthcare collaboration for dysmenorrhea management education. Keywords: Dysmenorrhea, non-pharmacological management, high school students, turmeric herbal remedy, menstrual pain relief